(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Endometriosis is a common gynecological disease that significantly impacts women’s health. It presents with dyspareunia, dysmenorrhea, chronic pelvic pain, and infertility. Globally, the prevalence of endometriosis is estimated to be 10 , with comprehensive literature on its % clinical presentation in developed countries. However, only scant literature exists in Africa. Objective: To determine the symptoms of endometriosis in indigenous African women. Methods: This was a prospective analytical cross- selection study that enrolled indigenous African women undergoing laparoscopic surgery in two tertiary hospitals in Nairobi, Kenya. The study population included women aged 18-49 years scheduled for laparoscopic surgery. Data on patient history, clinical, laparoscopic, and histopathological findings were entered and analyzed using the IBM statistical package for social sciences (SPSS), version 22.0. The statistical significance was set at p<0.05. Results: Between March 2018 and March 2021, 443 women were enrolled in this study. The mean age was 33. The prevalence of histologically confirmed endometriosis was 6.8. Chronic pelvic pain (scale % 8-10), dysmenorrhea, and dyspareunia were the significant symptoms of endometriosis (p<0.001). Nulliparous patients were more likely to develop endometriosis (OR=4.1 (1.6 10.2)). Women with menarche at ≤13 years had a significantly higher risk of developing endometriosis (p=0.001). There was no correlation between infertility and endometriosis (p=0.031). Conclusion: The prevalence of histologically confirmed endometriosis in indigenous Africans was 6.8 . % Endometriosis prevalence in Africa is comparable to the worldwide prevalence, and as such, with its morbidity, it warrants close attention. Chronic pelvic pain, dysmenorrhea, and dyspareunia are significant symptoms of endometriosis, and as such, patients with these symptoms should be investigated for endometriosis.